2015
DOI: 10.1002/psc.2786
|View full text |Cite
|
Sign up to set email alerts
|

Cecropin‐P17, an analog of Cecropin B, inhibits human hepatocellular carcinoma cell HepG‐2 proliferation via regulation of ROS, Caspase, Bax, and Bcl‐2

Abstract: Cecropin-P17 is a peptide derived from Cecropin B. In this study, we investigated the effects and relative mechanisms of Cecropin-P17 in a human liver cancer cell line (HepG-2) in vitro and in vivo. A cell viability assay, Annexin V/propidium iodide assay, western blot, flow cytometry, quantitative real-time polymerase chain reaction, and a tumor-xenograft model were applied to elucidate the mechanism exerted by Cecropin-P17 on HepG-2 cells. Cecropin-P17 significantly inhibited the proliferation of HepG-2 cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 27 publications
(30 reference statements)
0
16
0
Order By: Relevance
“…Increased Bax expression can prolong the patients’ survival in ovarian cancer [27, 28]. Cecropin-P17 significantly suppresses hepatic tumor growth in vivo by stimulating BAX and inhibition Bcl-2 expression [29]. The in vivo and in vitro binding assay proved that ZNF667 can directly bind to the Bax promoter [12].…”
Section: Discussionmentioning
confidence: 99%
“…Increased Bax expression can prolong the patients’ survival in ovarian cancer [27, 28]. Cecropin-P17 significantly suppresses hepatic tumor growth in vivo by stimulating BAX and inhibition Bcl-2 expression [29]. The in vivo and in vitro binding assay proved that ZNF667 can directly bind to the Bax promoter [12].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, Choi and Lee (2013) showed that when the first six amino acid residues (GWGSFF) of pleurocidin (Table 2) were truncated, the peptide lost its effect on ROS production (apoptosis), apparently because the N-terminus of pleurocidin contains a BH3-like motif (Table 2, underlined amino acids). Similarly, cecropin-P17 (Table 2) was shown to suppress the proliferation of HepG-2 cells by inducing apoptosis, which was dependent (among other things) on inhibiting Bcl-2 (Wu et al, 2015).…”
Section: Resultsmentioning
confidence: 97%
“…The effects of TT-1 on the activity of caspase-3 and -9 in TT cells were determined using a fluorometric assay kit (Calbiochem; EMD Millipore) according to the manufacturer's protocol as previously described (24). Briefly, TT cells were treated with TT-1 (0-8 µg/ml) for 48 h and harvested prior to the preparation of cell lysates.…”
Section: Western Blot Analysis For Bax and Bcl-2 Protein Expressionmentioning
confidence: 99%